An acetylated mannan isolated from Aloe vera induce colorectal cancer cells apoptosis via mitochondrial pathway. (1st September 2022) - Tong, Xueli; Lao, Chunqin; Li, Di; Du, Junxi; Chen, Jingmian; Xu, Weijie; Li, Lu; Ye, Huiling; Guo, Xiaofeng; Li, Jiejing
Abstract: The anti-cancer effects of Aloe vera barbadensis extract C (AVBEC) have been demonstrated in a previous study. However, the specific functional ingredient and mechanism remain undefined. This study aimed to evaluate the function and associated mechanisms of purified polysaccharide (ABPA1) from AVBEC on colorectal cancer. Here, we identify that ABPA1 can induce colorectal cancer apoptosis. In vivo, ABPA1 significantly suppressed tumor growth in an orthotopic colon cancer model. Mechanistically, ABPA1 alters mitochondrial membrane permeability by promoting Bax translocation while causing cytochrome-c release, which initiates the caspase cascade reaction. Additionally, we found that ABPA1 exerted distinct impacts on the mitochondrial metabolism of colorectal cancer cells. Our study elucidated the mechanism by which the polysaccharide ABPA1 induces apoptosis in colorectal cancer cells through the regulation of Bax and cytochrome-c mediated mitochondrial pathway, indicating that ABPA1 may be developed as a mitochondrial-targeting anti-cancer drug. Graphical abstract: Unlabelled Image